A Case Study at a Civil Aviation School on Using Problem-Based Learning to Enhance Creative, Critical, and Problem-Solving Skills - Harianto, Bambang Bagus; Suprianto, Bambang; Wardhono, Arie (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to find out how cadets' critical thinking, creativity, and problem-solving capabilities are affected by problem-based learning methodologies. The methodology for this investigation was quasi-experimental. The population used in this research was taken from second-semester cadets from seven academic programs. The samples used were three classes selected based on random sampling techniques, namely Airport Electrical Engineering (AEE) 48 cadets, Aircraft Engineering (A.E.) 48 cadets, and Airport Civil Engineering (ACE) 48 cadets. The data analysed are descriptive and inferential statistical data, which are analysed using MANOVA. Its findings showed that the implementation of PBL (experimental class) was better than DL (control class) in improving cadet capability, with a significance level of α = 0.05.